The manipulator tool state classification based on inertia forces analysis. (July 2018) - Gierlak, Piotr
Graphical abstract: Highlights: The database for analysis is obtained in a research environment. The inertia forces are registered and used for tool state analysis. The analysis of the signals is performed within the domain of time and frequency. The registered signals are represented with the use of selected features. The algorithm of the tool state classification is proposed. Abstract: In this article, we discuss the detection of damage to the cutting tool used in robotised light mechanical processing. Continuous monitoring of the state of the tool mounted in the tool holder of the robot is required due to the necessity to save time. The tool is a brush with ceramic fibres used for surface grinding. A typical example of damage to the brush is the breaking of fibres, resulting in a tool imbalance and vibrations at a high rotational speed, e.g. during grinding. This also results in a limited operating surface of the tool and a decrease in the efficiency of processing. While an imbalanced tool is spinning, fictitious forces occur that carry the information regarding the balance of the tool. The forces can be measured using a force sensor located in the end-effector of the robot allowing the assessment of the damage to the brush in an automatized way, devoid of any operator.